Características das estruturas produtivas agrícolas regionais brasileiras entre 1995 e 2021 - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The objective of this investigation is to verify how the agricultural productive structures were characterized, in their regional multiscale forms between 1995 and 2021, in what refers to their location and specialization aspects. To this end, it is observed that markets, by leading the style of regional development, accelerated the process of modernization of national agricultural structures, but increasingly accentuating structural, productive and regional heterogeneities. Thus, the logic of the market, commanded by national and international financial capital, overlapped the interests of the national state, establishing a pattern of national and regional agricultural production that is strongly linked with the centers of international decisions, in particular, those related to the Chinese economy. In this way, the agricultural crops that presented the greatest expressions were those related to soy, corn, sugar cane and cotton, which are raw materials for the main links of the regional, national and international production chains.
Keywords: R11; 330; agricultural structure; export crops; midwest